Application of ultrasound in assessment of acute lung injury in mice - An-Xia Deng; Ling Zhao; Amanguli Ruze; Qiu-Lin Li; Bang-Hao Zhao; Su Hu; Min-Tao Gai; Hong-Li Wang; Qiao-Ling Yao; Xiao-Ming Gao (PLoS ONE, 2025)
This study evaluated the effectiveness of non-invasive ultrasound technology in monitoring pulmonary edema in a mouse model of acute lung injury (ALI). Male C57BL/6J mice were instilled through the trachea with lipopolysaccharide (LPS, 5 mg/kg, single dose) to induce ALI. The change in B-lines (an ultrasound sign) were monitored using the Vevo 3100 system and the lung ultrasound (LUS) score was generated to quantify the severity of edema, meanwhile lung function was assessed by whole-body plethysmography (WBP) and the progression of ALI was tracked by lung weight and histopathological analysis. LUS detection revealed that non-converging B-lines appeared on the first day, followed by an increase in the number of B-lines that began to converge, peaking on the day-3 and then the number of B-lines decreased, almost disappearing by the 11 days after LPS intervention. Significant changes in lung functional parameters were recorded during 6–24 h with most parameters returning to baseline levels at day-3. Morphological and weight assessments of the lung showed that most severe lung congestion and increased weight at day-3 and returning to normal by 11 days. Histopathological examination unveiled that LPS-induced inflammation was characterized by increased cellular infiltration, thickening of alveolar septa, vascular congestion, and atelectasis, which were most severe on days 3–5 and then gradually improved. A positive correlation between LUS score and the lung injury index (r = 0.783, P < 0.001) or the lung weight-to-tibial length ratio (r = 0.695, P < 0.001) was observed, reflecting a sensitivity of LUS to the severity of edema. In addition, at 24 h following LPS intervention, the LUS score was also positively or negatively correlated with a series of lung functional indices. In conclusion, the study demonstrated that LUS is an effective, reliable and non-invasive tool for monitoring pulmonary edema in a mouse model of ALI. The significant correlations between LUS scores with various pathophysiological parameters, highlight its potential in assessing the severity of ALI in mice.